Chromosomes Characteristics of Vegetable Fern (Diplazium esculentum) in Rinjani Mountain National Park - Pratiwi, Elsa; Mertha, I Gde; Sukarso, A. A. (Jurnal Biologi Tropis, 2024)
Vegetable fern (Diplazium esculentum) is one type of fern that is utilised by the Indonesian people as one of the food ingredients. Chromosomes are genetic information in cells that are the basic unit of life. The purpose of this study was to determine the number of chromosomes and mitotic index of vegetable spikes (D. esculentum) at various altitudes in Mount Rinjani National Park. The type of research is quantitative research that describes a situation using numbers factually, systematically and accurately quantitative data of vegetable fern chromosomes (D. esculentum). The method used in the research is Squash method. The results showed no difference in the number of chromosomes of vegetable spikes (D. esculentum) at an altitude of 292 masl, 538 masl, 703 masl and 1417 masl. The number of chromosomes of vegetable spikes at all altitudes 2n = 82 (diploid) x = 41. The mitotic index of vegetable spikes showed results that were not significantly different at altitudes of 292 masl, 538 masl, 703 masl and 1417 masl.